An interactive multiobjective approach to harvest decisions in forest planning - Krcmar-Nozic, E; Knooten, G.C. van; Vertinsky, I. (British Columbia Univ., Vancouver (Canada). Forest Economics and Policy Analysis Research Unit); Brumelle, S (Scandinavian journal of forest research, 1998)
A hierarchical approach to forest planning is formulated, where harvest schedules are first determined, followed by a decision about harvest methods (harvest regime). Choice of harvest methods is particularly important because of concerns about harvest-related site disturbance. In the decision model developed in this article, determination of a harvest regime is expressed as a multiple-objective decision incorporating maximization of net present value and minimization of cumulative site disturbance for different site classes, subject to maintaining high levels of production, an even flow of timber, and avoiding adjacency violations. The search for preferred harvest regimes is performed interactively over a set of non-dominated harvest schedules with alternative aspiration levels identified for the various objectives to reflect values of different stakeholders.